Implementasi Model Asinkronus dalam Pembelajaran Bahasa Arab Qur’ani: Strategi Pemahaman Semantik Al-Qur’an pada Ummahāt: MODEL PEMBELAJARAN ASINKRON: STRATEGI PENINGKATAN KOMPETENSI SEMANTIK AL-QUR’AN PADA KALANGAN UMMAHAT - Rahman Hakim; Nahdliyyatul Azimah (Muaddib: Journal of Arabic Language and Literature, 2026)
Quranic Arabic learning for ummahāt (mothers) is often hindered by domestic time constraints and the prevalence of rigid syntactic approaches, which fail to bridge the gap between literal translation and contextual understanding. This study aims to evaluate the implementation of an asynchronous learning model focused on semantic strategies to address these accessibility and cognitive barriers. Using a qualitative-descriptive approach with a case study design, data were gathered through participatory observation on YouTube and WhatsApp, semi-structured interviews, and learning documentation. The results indicate that the asynchronous transformation provides cognitive flexibility, allowing learners to engage in self-reflection on vocabulary (mufradāt), meanings (ma’āny), and concise exegesis (tafsīr ijmāly) within their domestic schedules. This model effectively internalizes Quranic values through repetitive multimedia exposure, shifting the learning focus from literal translation to tadabbur (reflective contemplation). The study concludes that digital learning serves as an innovative solution to bridge the gap in Arabic literacy and textual comprehension among ummahāt.